Social Complexity: Incipience, Emergence, and Development on Prehistoric Cyprus - Knapp, A. Bernard (Bulletin of ASOR, 1993)
The study of social complexity on prehistoric Cyprus-from the Neolithic Period through the Bronze Age-is relatively new to Cypriot archaeology, and results chiefly from fieldwork and research conducted over the past decade. This study examines the notion of social complexity in general, and its use by archaeologists working on Cyprus (especially those who have contributed to this issue of BASOR). Following that, an attempt is made to define in chronological and material terms the incipience (Mid-Late Chalcolithic), emergence (Prehistoric Bronze Age), and full development (Protohistoric Bronze Age) of social complexity on Cyprus. Finally, the implications of these dynamic stages in the politico-economic and cultural development of prehistoric Cyprus are discussed from a social perspective, in terms of differing power strategies.